Development of polyvinyl alcohol nanofiber scaffolds loaded with flaxseed extract for bone regeneration: phytochemicals, cell proliferation, adhesion, and osteogenic gene expression - Abdelaziz, Ahmed G.; Nageh, Hassan; Abdalla, Mohga S.; Abdo, Sara M.; Amer, Asmaa A.; Loutfy, Samah A.; Abdel Fattah, Nasra F.; Alsalme, Ali; Cornu, David; Bechelany, Mikhael; Barhoum, Ahmed (Frontiers in Chemistry, 2024)
Introduction: Bone tissue engineering seeks innovative materials that support cell growth and regeneration. Electrospun nanofibers, with their high surface area and tunable properties, serve as promising scaffolds. This study explores the incorporation of flaxseed extract, rich in polyphenolic compounds, into polyvinyl alcohol (PVA) nanofibers to improve their application in bone tissue engineering. Methods: High-performance liquid chromatography (HPLC) identified ten key compounds in flaxseed extract, including polyphenolic acids and flavonoids. PVA nanofibers were fabricated with 30 wt.% flaxseed extract (P70/E30) via electrospinning. We optimized characteristics like diameter, hydrophilicity, swelling behavior, and hydrolytic degradation. MG-63 osteoblast cultures were used to assess scaffold efficacy through cell adhesion, proliferation, viability (MTT assay), and differentiation. RT-qPCR measured expression of osteogenic genes RUNX2, COL1A1, and OCN. Results: Flaxseed extract increased nanofiber diameter from 252 nm (pure PVA) to 435 nm (P70/E30). P70/E30 nanofibers showed higher cell viability (102.6% vs. 74.5% for pure PVA), although adhesion decreased (151 vs. 206 cells/section). Notably, P70/E30 enhanced osteoblast differentiation, significantly upregulating RUNX2, COL1A1, and OCN genes. Discussion: Flaxseed extract incorporation into PVA nanofibers enhances bone tissue engineering by boosting osteoblast proliferation and differentiation, despite reduced adhesion. These properties suggest P70/E30’s potential for regenerative medicine, emphasizing scaffold optimization for biomedical applications.